Effects of constraint-induced movement therapy on activity and participation after a stroke: Systematic review and meta-analysis - de Azevedo, Joyce Araújo; Barbosa, Felipe Douglas Silva; Seixas, Valquiria Martins; da Silva Scipioni, Kelly Regina Dias; Sampaio, Priscila Yukari Sewo; da Cruz, Daniel Marinho Cezar; Piscitelli, Daniele; Chui, Kevin K.; de Freitas Zanona, Aristela (Frontiers in Human Neuroscience, 2022)
Hemiparesis is the main sensorimotor deficit after stroke. It can result in limitations in Activities of Daily Living (ADL) and social participation. Hemiparesis can be treated with behavioral techniques of intensive use of the affected arm, such as constraint-induced movement therapy (CIMT), however, it remains unclear whether motor improvement can lead to increases in the domains of activity and participation. Objective. Identify whether CIMT is superior to usual techniques to enhance activity and participation outcomes in stroke survivors. Methods. A systematic review with meta-analysis was conducted, based on the PRISMA guidelines. Search databases were: PubMed, LILACS, Embase, SciELO, Cochrane Library, Scopus, Medline, and Web of Science, with no language restriction. Meta-analysis was performed with Review Manager (version 5.3), significance level p ≤ 0.05. Results. A total of 21 articles were included for analysis. Superior effects were observed on motor function and performance in activities of daily living of individuals treated with CIMT. The outcomes measures utilised were: Fugl-Meyer Assessment (p=0.00001); Wolf motor function test (p=0.01); Modified Barthel Index (p=0.00001); Motor Activity log (MAL) Amount of use (AOU) (p=0.01); MAL Quality of movement (QOM) (p=0.00001); Action Research Arm Test-ARAT (p=0.00001); and FIM (p=0.0007). Conclusion. Our results show that CIMT results in more significant gains in the functional use of the upper limb in ADL and functional independence, demonstrating superior activity and participation results in stroke survivors when compared to conventional therapies.